Desempenho produtivo, eficiência digestiva e perfil metabólico de juvenis de tambaqui, Colossoma macropomum (Cuvier, 1818), alimentados com diferentes taxas carboidrato/lipídio - Almeida, Luciana Cristina de (2011)
Increase of dietary lipid and carbohydrate with concomitant reduction of protein level is a promising prospect to suply the fish energetic demand and to spare dietary protein to the growth. Study of digestive enzymes secretions combined with growth parameters and metabolism can help solve many nutritional problems in the aquaculture. The aim of this work was investigating growth, digestive efficiency and metabolic responses of juvenile tambaqui (Colosssoma macropomum) fed with 3 carbohydrate/lipid ratios (CHO/L): 30,5/13,7% (diet I); 40,5/9,1% (diet II); 50,0/4,8% (diet III). The diets were isoenergetic and isoproteic. The experiment was carried out in the facilities of the Adaptive Biochemistry Laboratory, Genetics and Evolution Department at Federal University of São Carlos. The following parameters were assayed: fish growth, digestives enzymes (unspecific proteases, trypsin, chymotrypsin, unspecific lipase, amylase and alkaline phosphatase), metabolites (glucose, lactate, pyruvate, ammonia, protein, fat acids, triglycerides, amino acids and glycogen), and the enzymes LDH, MDH and GDH. Fish fed with the diet II presented the highest values of weight gain, length gain, relative food-intake ratio, and condition factor. However, fish fed with diet III depicted the worst performance and the lowest HIS when compared to fish fed with other diets. Tambaqui digestive enzymes were responsive to dietary carbohydrate/ lipid ratios. Fish from diet III showed significantly reduction of alkaline phosphatase activity and T/C ratio; moreover showed increased of lipase activity (in all gastrointestinal tract) and amylase activity (stomach and anterior intestine). In relation to metabolism, it was detected lipolysis in livers in accordance with the increase of the dietary CHO/L ratio. Muscular glycogenesis, lipolysis and gluconeogenesis from amino acids to energetic supply were observed in fish fed with higher dietary CHO/L ratio. The plasma metabolic profile reflected the blood metabolite delivery function among tissues underlining biochemical adaptations due to alterations in the fish feeding. In conclusion, dietary carbohydrate to lipid ratios induced digestive enzymes of tambaqui. The increase of CHO/L ratio resulted in fish growth decrease, augmented the liver lipolysis, increase the muscular glucogenesis, lipolysis and the gluconeogenesis. The fish metabolism seemed to be predominantly lipolitic suggesting that, in this species, lipids are more efficiently used to energy storage than carbohydrates. Diet III deprived the fish of energy resource resulting in protein utilization for this purpose. Tambaqui spared protein to growth utilizing mainly carbohydrate and lipid when fed with diet II.